(untitled) (Research, Society and Development, 2022)
The COVID-19 pandemic required from Primary Health Care a readjustment in care regarding the approach of the Community Health Agent regarding home visits and other activities. This article aimed to report the experience of creating and developing educational videos, in a partnership between the University and Primary Health Care, adopted as facilitating instruments for the work of Community Health Agents in the face of the COVID-19 pandemic. . The applied methodology refers to an experience report of technological innovation of the elaboration of educational videos by university professors and students, destined to the Community Health Agents in their new work routine. Measures to contain the epidemic were taken from government and health agencies, covering institutional, professional and community demands. The videos were made available for the coordination of the APS of each municipality, accompanied by an informative document on the contents covered in each video. health during the period of social isolation. The work made it possible to form partnerships with municipal health departments, which provided their Community Health Agents with the products of this work. The institutional communication channels of the Federal University of São João del-Rei, as well as the social media platforms of those involved and supporters, also became a space for dissemination.